Socioeconomic Status and Waiting Times for Health Services: Current Evidences and Next Area of Research. (August 2019) - Landi, Stefano; Ivaldi, Enrico; Testi, Angela
Waiting times are an issue in many countries, excessive waiting for treatments may deteriorate patient's health status and reduce treatment effectiveness potentially, becoming a barrier in the access to health care services. Waiting time to be equitable should be related only to the health need, people with the same health need have to wait the same time, without any difference due to socioeconomic status. In the commentary, the results of the extensive literature review and policy implications are discussed.